Waqf on Health: A Bibliometric Review using R - Rusydiana, Aam Slamet; Laila, Nisful; Herianingrum, Sri (Journal of Islamic Economics Literatures, 2023)
This study aims to determine the development and map of research trends with the theme waqf on health published by well-known journals. The data used in this study were 42 indexed research publications with the theme waqf on health in the period 1994-2020. The map of research development in the field of waqf on health is obtained through the export process which will be processed and analyzed using the R Biblioshiny application program. The results showed that the number of waqf on health research publications experienced a development trend with a stagnant increase. Besides, the results show that the journal with the most publication and impact is the Journal of Islamic Accounting and Business Research. The country that contributes the most to waqf on health research is Malaysia. The results of this study also indicate that the most widely used topic keywords are Waqf, Islamic, Case, and Malaysia.